Pharmacognostical and Preliminary Phytochemical Screening on Leaves of Trianthema decandra Linn. - K, Yamini (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Phytochemical studies of the Trianthema decandra[1,2] Leaves were carried out in present study. Morphology of the plant, microscopy of the leaves. Total ash, acid insoluble ash, water insoluble ash and sulphated ash were 16.33%w/w, 3.33%w/w,4.00%w/w,2.35%w/w respectively. The extractive values i.e. Methanol, petroleum ether, n-Hexane, ethyl acetate, ethanol and aqueous extract were 40%w/v,8%w/v,20%w/v,12%w/v,10%w/v,20%w/v. The preliminary phytochemical studies were performed with various reagents and chemicals on plant methanolic extract in order to determine the various secondary metabolites. By performing the tests it was concluded that carbohydrates, protein, volatile oils, glycosides, saponins, flavanoids, alkaloids are present.